To determine the equation of the translated line, we start with the original line given by \( y = -x + 1 \).
-
Translation 1 unit to the right: Translating a line 1 unit to the right means we replace \( x \) with \( x - 1 \) in the equation. \[ y = - (x - 1) + 1 = -x + 1 + 1 = -x + 2 \]
-
Translation 2 units up: Now we need to translate the line \( y = -x + 2 \) 2 units up. To do this, we add 2 to the entire equation: \[ y = -x + 2 + 2 = -x + 4 \]
Thus, the equation of the translated line is:
\[ y = -x + 4 \]
Looking at the provided options, the correct answer is:
C. \( y = -x + 4 \).